Development of an mHealth Intervention (iSTEP) to Promote Physical Activity among People Living with HIV. (November 2015) - Montoya, Jessica L.; Wing, David; Knight, Adam; Moore, David J.; Henry, Brook L.
A randomized controlled trial is being conducted in the United States to test the efficacy of a personalized interactive mobile health intervention (iSTEP) designed to increase physical activity (PA) and improve neurocognitive functioning among HIV-positive persons. This article describes an initial qualitative study performed to develop iSTEP for the HIV-positive population, including assessment of PA barriers and facilitators. Two focus groups, with 9 and 12 unique HIV-positive individuals, respectively, were administered to evaluate barriers limiting PA and potential iSTEP content created to encourage greater PA. Group discussions revealed prominent PA barriers, including HIV symptoms (neuropathy, lipoatrophy), antiretroviral medication effects, and fatigue; significant PA facilitators included self-monitoring and family support. Participants provided feedback on strategies to increase PA and expressed positive support for a mobile intervention adapted to personal priorities. These findings will assist the development of novel PA interventions focused on treating the epidemic of HIV-associated neurocognitive disorders.